2005
DOI: 10.1002/rsa.20098
|View full text |Cite
|
Sign up to set email alerts
|

On the asymptotics of fault probability in least‐recently‐used caching with Zipf‐type request distribution

Abstract: ABSTRACT:We consider the least-recently-used cache replacement rule with a Zipf-type page request distribution and investigate an asymptotic property of the fault probability with respect to an increase of cache size. We first derive the asymptotics of the fault probability for the independentrequest model and then extend this derivation to a general dependent-request model, where our result shows that under some weak assumptions the fault probability is asymptotically invariant with regard to dependence in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 23 publications
4
17
0
Order By: Relevance
“…We find that asymptotic characteristics of LRU are often preserved in our fluid limit. Specifically, we will see that, as K → ∞,p (∞) is asymptotically insensitive to particular dependencies in the request processes when the request rates have a heavy tail (Theorem 3), which agrees with the findings forp in [3], [18]. We also find that the asymptotic analysis ofp (∞) appears to be simpler than a corresponding analysis ofp.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…We find that asymptotic characteristics of LRU are often preserved in our fluid limit. Specifically, we will see that, as K → ∞,p (∞) is asymptotically insensitive to particular dependencies in the request processes when the request rates have a heavy tail (Theorem 3), which agrees with the findings forp in [3], [18]. We also find that the asymptotic analysis ofp (∞) appears to be simpler than a corresponding analysis ofp.…”
Section: Introductionsupporting
confidence: 82%
“…, N are conditionally independent given J(·). Note that Ψ is stationary, which is also assumed in [3], [9], [11], [18], so that the stationary miss probability exists (see Lemma 2.1 from [18]) and agrees with the average miss probability.…”
Section: Asymptotic Analysis With Fluid Limitmentioning
confidence: 72%
See 2 more Smart Citations
“…These demonstrated performance improvements, both analytical and experimental, as well as the simplicity of implementation, suggest a potential use of the proposed PAC policy for practical purposes. Given the analytic approach established in our recent work on the analysis of the LRU policy in the presence of dependent requests [12] and variable page sizes [13] (see also [17]), it can be shown that analogous results hold for the PAC algorithm as well. In the context of the ordinary MTF with lighter tailed request distributions, the asymptotic fluid limits of the search cost derived in [10] could be analogously extended to the PAC policy as well.…”
Section: Discussionmentioning
confidence: 82%